Australia's Unprecedented Future Temperature Extremes Under Paris Limits to Warming. Issue 19 (13th October 2017) - Lewis, Sophie C.; King, Andrew D.; Mitchell, Daniel M.
Abstract: Record‐breaking temperatures can detrimentally impact ecosystems, infrastructure, and human health. Previous studies show that climate change has influenced some observed extremes, which are expected to become more frequent under enhanced future warming. Understanding the magnitude, as a well as frequency, of such future extremes is critical for limiting detrimental impacts. We focus on temperature changes in Australian regions, including over a major coral reef‐building area, and assess the potential magnitude of future extreme temperatures under Paris Agreement global warming targets (1.5°C and 2°C). Under these limits to global mean warming, we determine a set of projected high‐magnitude unprecedented Australian temperature extremes. These include extremes unexpected based on observational temperatures, including current record‐breaking events. For example, while the difference in global‐average warming during the hottest Australian summer and the 2°C Paris target is 1.1°C, extremes of 2.4°C above the observed summer record are simulated. This example represents a more than doubling of the magnitude of extremes, compared with global mean change, and such temperatures are unexpected based on the observed record alone. Projected extremes do not necessarily scale linearly with mean global warming, and this effect demonstrates the significant potential benefits of limiting warming to 1.5°C, compared to 2°C or warmer. Plain Language Summary: Extreme temperatures affect ecosystems, infrastructure, and human health. Understanding how climate change is impacting climate extremes and how extremes will change under future global warming are important scientific research questions. Previous scientific studies have focused on how current temperature extremes have been impacted by climate change, or on how the frequency of these current extremes will change in the future. This study takes a different approach and examines how the severity of future temperature extremes might change in the future. We assess the possible severity of Australian temperature extremes under the limits to warming that are described in the Paris Agreement (1.5°C and 2°C of global warming above the period prior to industrialization). This study finds that the magnitude of future temperature extremes for Australia does not necessarily increase at the same rate of global warming. The severity of possible future temperature extremes simulated by climate models in this study poses serious challenges for preparedness for future climatic change in Australia. For example, daily temperature extremes of 3.8°C above existing records are simulated for Australian states, even under the ambitious Paris efforts to curb global warming. Key Points: Possible magnitude of future extreme temperatures are assessed under 1.5 and 2°C of global warming Daily temperatures of 3.8°C above existing records are simulated for Australian states Future extreme events do not necessarily scale linearly with global warming or previous records